Mapping of the Stable Articular Surface and Available Bone Corridors for Cup Fixation in Geriatric Acetabular Fractures. Issue 13 (1st July 2020) - T. Marmor, Meir; Huang, Adrian; Knox, Riley; Herfat, Safa; Firoozabadi, Reza
Abstract : Background: The optimal treatment of acetabular fractures in the senior cohort is undetermined. Total hip arthroplasty in the setting of an acetabular fracture is increasing in popularity. However, there is concern regarding the fixation of a prosthetic cup in a fractured acetabulum. The purpose of this study is to map the area of stable articular surface and bone corridors available for cup fixation in this fracture cohort. Methods: CT scans of acetabular fractures in 131 consecutive geriatric patients older than 65 years from two level 1 academic trauma centers were analyzed. Acetabular fractures were classified using the Letournel classification, the available stable articular surface, and the bone corridors available for fixation. Results: Fractures involving the anterior column were the most common fracture type seen. The dome only pattern was the most common stable articular surface pattern. The sciatic corridor was available for fixation in all fracture types, followed by the gluteal pillar corridor. Most fractures had at least two corridors (93%) available for screw fixation. Conclusions: The findings of this study may aid in the development and evaluation of fixation strategies for acetabular cups allowing geriatric acetabular fracture patients earlier weight bearing after primary hip arthroplasty.